2021
DOI: 10.55563/clinexprheumatol/mvcai5
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the EULAR Sjögren's Syndrome Patient-Reported Index in primary Sjögren's syndrome

Abstract: Objective. The EULAR Sjögren's Syndrome Patient-Reported Index (ESS-PRI) is a validated tool for measuring pain, fatigue and dryness in primary Sjögren's syndrome (pSS). We evaluated its association with disease and non-disease related variables, and its variation though the follow-up. Methods. We included 130 pSS patients who were interviewed to register demographics, schooling, smoking, menopause, body mass index, disease duration, use of hormonal replacement, associated sicca drugs, prednisone, immunosuppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In the study by Seror et al (12), 38% of patients were in an acceptable symptom state according to ESSPRI in the ASSESS cohort, and this was 32% in the EULAR cohort, which was more comparable to the findings in our study. Another observational cohort study, showed that 38% had an ESSPRI score <5, which was also comparable to our cohort (19). We found that PASS was independently associated with ESSPRI and disease duration, although the explained variance of these parameters to predict PASS was low (Nagelkerke R 2 0.31).…”
Section: Patient Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…In the study by Seror et al (12), 38% of patients were in an acceptable symptom state according to ESSPRI in the ASSESS cohort, and this was 32% in the EULAR cohort, which was more comparable to the findings in our study. Another observational cohort study, showed that 38% had an ESSPRI score <5, which was also comparable to our cohort (19). We found that PASS was independently associated with ESSPRI and disease duration, although the explained variance of these parameters to predict PASS was low (Nagelkerke R 2 0.31).…”
Section: Patient Characteristicssupporting
confidence: 89%
“…Since previous research showed that subjective and objective dryness measurements also show poor correlations, this is not an unexpected finding (24). However, an observational cohort study in 130 pSS patients found that patients with an ESSPRI≥5 had lower UWSF scores than patients with ESS-PRI<5 (19). Since the ESSPRI includes a question specifically about dryness and the PASS is a global question, this might explain this difference.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In the present study, salivary protein concentrations significantly correlated with the ESSPRI pain subscore. A correlation between increasing ESSPRI scores and a decrease in non-stimulated total salivary flow has been reported in the literature [ 34 ]. Interestingly, ESSPRI dryness did not correlated with tear or salivary flow, but ESSPRI pain did [ 35 ].…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Sandhya et al reported a positive correlation of salivary KFLC with features of dry mouth, but beyond that, there were no other statistically significant correlations of salivary FLC with sicca symptoms [ 17 ]. In addition, several studies found a weak correlation between objective and subjective indices of ocular dryness [ 33 , 34 ]. On the one hand, it could be hypothesized that the lower salivary fluid production in patients with SS leads to more concentrated saliva, and thus to increased FLC concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation